Modelling of integrity infringement on the basis of the risk tree and rare events modeling methods - Харченко, В.П.; Знаковська, Є.А. (Proceedings of National Aviation University (archive), 2005)
The risk tree method improvement with the help of a rare events modelling at optimum subsidiary sample was suggested.